Transplantation of a free fillet flap from discarded fingers for repair of a finger pulp skin defect: a case report - Zhou, Xianting; Zhang, Chenxi; Fan, Xuekai; Cai, Xiaoming; Wang, Xin; Pan, Jiadong (Frontiers in Surgery, 2024)
Background: Replantation represents a treatment option for patients with severed finger pulps.Replantation is an ideal method for treatment of severed finger pulp. However, in some cases, replantation is a challenging task. Case presentation: We report a successful case of finger pulp reconstruction of the ring finger using free flaps from a nonreplantable index finger in a spare-parts procedure. A 43-year-old worker accidentally injured the index, middle and ring fingers of his left hand on a machine turntable. The severed index and middle fingers and the distal pulp of the ring finger could not be replanted in situ due to extensive contusion of blood vessels and soft tissues. After vascular and nerve anastomosis, a free skin flap isolated from the nonreplantable index finger was transplanted to the wound of the distal pulpal defect of the ring finger. The flap survived completely postoperatively. Six months after the operation, only a slight deformity of the ring finger was observed. Moreover, sensation of the digit recovered well. Six months after the operation, only a slight deformity of the digit was observed, and recovered well digit sensation. Conclusions: Spare-part surgery is a surgical approach that effectively saves and utilizes tissue that would otherwise be discarded in cases of severe limb trauma. This idea may be applied to treatment of severe injuries to multiple fingers. Additionally, in the process of tissue transplantation and repair, attention should be given to protecting the tissue in the recipient area to avoid damage to the original undamaged tissue structure, which can adversely affect healing and recovery of the tissue.